Oil Revenue, Institutions and Macroeconomic Indicators in Nigeria (2013)
The influx of massive revenues during periods of abnormally high oil prices creates enormous challenges for policy-makers in oil-producing countries. In Nigeria, the prudent utilisation of oil revenues has remained elusive for policy-makers over time. While the country has earned sizeable oil revenues from its natural endowment, poverty and income inequality have been persistent. This study tests the sensitivity of several important macroeconomic indicators to oil revenue shocks. We additionally test for the effect of ‘institutional quality’, in recognition of the important role played by the domestic institutional context in shaping the policy responses adopted by successive Nigerian governments to oil windfalls over time. The sensitivity analysis supports the general view that fluctuations in oil revenues have resulted in inflation, lower output growth and real exchange rate appreciation in Nigeria. More importantly, the aforementioned institutional variable is found to be very significant. This finding is consistent with the general assessment of fiscal performance in Nigeria during oil windfalls as being driven by domestic institutional dynamics. Ostentatious public consumption widened fiscal deficits, and government spending has been highly pro-cyclical during windfall episodes. In conclusion, the study offers appropriate policy recommendations, which could be adopted to enhance the management of future oil windfalls in Nigeria.